Molecular Dynamics Simulation of the Implantation of b-Oriented ZSM-5 Film Modified α-Quartz Substrate Surface With Different Modifiers - Wu, Jiaxin; Meng, Xianliang; Chu, Ruizhi; Yu, Shi; Wan, Yongzhou; Song, Chengcheng; Zhang, Guifeng; Zhao, Tong (Frontiers in Chemistry, 2019)
In this study, we investigated the structure-absorption relationship of common surface modifiers of chitosan (CTS), polyvinyl acetate (PVA) and titanium dioxide (TiO2) with α-quartz surface using molecular dynamics simulation. And the orientations and combinations derived from structures between modified α-quartz and ZSM-5 crystallites were also investigated. The results show that PVA is a non-linear organic macromolecule with a large amount of hydroxyl groups on its surface, which is easy to adhere to the surface of the substrate and agglomerate. CTS is a straight-chain structure containing a large number of hydroxyl and amino groups, which is easy to accumulate and spread on the surface of the substrate. TiO2 not only forms hydrogen bonds and complexes with the substrate, but also interacts with each other to form a dense modifier layer. We observed that a large number of stable Ti-O-Si chemical bonds formed between the modified layer of inorganic small molecule TiO2 and the surface of α-quartz, which compacted and stabilize the attached ZSM-5 film. Moreover, the orientation angle of ZSM-5 nanocrystalline nucleus on the modified α-quartz was computed which confirmed that the b-axis orientation of ZSM-5 nanocrystalline nucleus was the highest on the surface of the substrate modified by TiO2. We discussed the influence of the modified temperature of modifiers in the constructed materials and we have observed the adsorption state differences of TiO2 at different modified temperatures. We also discussed the catalytic properties of the materials prepared by the corresponding methods in conversion of methanol to aromatics (MTA) reaction. These results agree with our previous experimental data. By employing molecular dynamics simulation, we have obtained more precise conclusive information of b-oriented growth of ZSM-5-crystallites which highly depends on the surface modifiers.